Effects of troponin C isoform on the action of the cardiotonic agent EMD 57033. - Lipscomb, S; Preston, L; Robinson, P; Redwood, C; Mulligan, I; Ashley, C (2005)
The effects of the cardiotonic potentiator EMD 57033 on different TnC (troponin C) isoforms were investigated. Endogenous skeletal TnC was extracted from glycerinated, permeabilized rabbit psoas fibres and replaced with either purified native rabbit psoas TnC (fast TnC) or human recombinant cTnC (cardiac TnC) (3 mg/ml in relaxing solution for 30 min). In both conditions, 10 microM EMD 57033 increased maximal calcium-activated force (Pmax) and gave a leftward shift in the pCa-tension curve. With cTnC, the increase in Pmax was much greater (228%) compared with the effect seen for fast TnC (137%), which was the same as that in unextracted control fibres. When the whole troponin was replaced rather than just TnC, the effects of EMD 57033 on fibres replaced with cTn were the same as with the cTnC subunit alone, except that the force at low Ca2+ concentrations was not increased as much. If TnC was only partially extracted, it was found that the degree of extraction did not influence the effect of EMD 57033, except when force was decreased to below 10% of the pre-extraction Pmax. Dynamic stiffness was not altered by EMD 57033 in any of the preparations. The rate of tension recovery following a release-restretch method (ktr) was decreased by EMD 57033. We conclude that EMD 57033 acts by a rate-modulating effect, and that the quantitative response of this effect is dependent on the TnC isoform present.